Lise Haimestad, Vladimir F. Stolba, A.N.Sсeglov (Eds.). Panskoe I. Vol. 1. The Monumental Building U 6 - Буйських, A.B.; Зубар, В.М. (Археологія, 2003)
Рецензія на книгу: Lise Haimestad, Vladimir F. Stolba, A.N.Sсeglov (Eds.). Panskoe I. Vol. 1. The Monumental Building U 6. Aarhus University Press, 2002. 368 P 191 PI ISBN 8772887702.